Bibliometrics of Community-Based Tourism Research in Developing Countries - Loso Judijanto (Westscience Press, 2026)
This study aims to map and analyze the intellectual structure and research trends of community-based tourism (CBT) in developing countries through a bibliometric approach. Using publication data retrieved from the Scopus database, this research applies VOSviewer to examine keyword co-occurrence, overlay visualization, density mapping, co-authorship networks, institutional collaboration, and country collaboration patterns. The findings reveal that community-based tourism, tourism development, sustainability, and ecotourism represent the core themes shaping the field. Early research primarily focused on conservation and protected areas, while more recent studies emphasize poverty alleviation, stakeholder engagement, and local community empowerment within sustainable tourism frameworks. Collaboration analysis indicates that developed-country institutions still play a bridging role in global research networks, although emerging contributions from developing regions are becoming more prominent. Overall, this study highlights the multidisciplinary evolution of CBT research and identifies future research opportunities related to governance, institutional capacity, and inclusive tourism development strategies. The results provide valuable insights for scholars, policymakers, and practitioners seeking to advance sustainable tourism initiatives in developing country contexts.